Nahwu Sufistik: Kajian Tasawwuf dalam Kitab Nahw Al-Qulub Karya Imam Al-Qusyairi - Khaerul Anwar (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2021)
Nahwu Sufi is the nahwu book by Imam al-Qusyairi whose writing seems unique and interesting to be studied more deeply. Imam al-Qusyairi tries to combine two disciplines, namely nahwu and tasawuf. But in this case Imam al-Qusyairi gave a new color to the Islamic discipline. In this book, nahw al-Qulub begins with an explanation of tauhid or affirmation to God, then the exoteric meaning of the word (zahir) is explained, which then explains the meaning of the word according to the perspective of Sufi scholars, namely esoterik (inner). In the book Nahwul Qulub explains how humans get closer to the Creator, human spiritual journey, and provides an overview of the state and life in this world towards eternal life. This type of library research or library research, which takes several sources of data from various theories in the literature. The result of this research is that Imam al-Qusyairi gives an idea that the elements of Sufism can be incorporated into various kinds of other sciences and there is no conflict whatsoever between Sufism and other sciences. With the presence of Nahwu Sufi this is not to eliminate nahwu in general, but with the existence of this Sufi nahwu, it gives a new color to nahwu science so that learners can learn it more enthusiastically. In this book Nahwul Qulub teaches us about ethics in life, teaches how to clean ourselves, heart and mind and get closer to or worship God. It also teaches us to always organize our hearts, words, attitudes and actions in daily life, so that everything we do is in accordance with the guidance of religious shari'ah